Educational Environment in the Quran - Aminah, Lilik (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
Educational environment is needed in the education process, because the educational environment serves to support the process of teaching and learning. The Environment of education is not described in the Qur'an explicitly, but there are several signs that indicate the presence of the educational environment. This writing is carried out through a literature study which is carried out by examining the concepts and theories used based on the available literature, including articles published in scientific journals that contain theories relevant to research problems. The family is the first educational environment where children get an education. At this point in the family laid the foundations of a child's personality. TheSchool as second in environment that developing the potential environmental grounds owned by the child. School is an environment where students absorb academic values including socializing with teachers and school friends. The Society is an educational institution after family and school. The shades of various education received by students in the community, covering all areas of both habit formation, the formation of knowledge, attitudes, interests, and the establishment of morality and religion. The natural environment is also used as a source of learning.